Judicial decisions in the ancient Near East - Démare-Lafont, Sophie; Fleming, Daniel E. (Writings from the ancient world, 2023)
"This volume presents the first broadly inclusive collection, with accessible text and English translation, of documents related to judicial decisions in the ancient Near East, the oldest setting for such writing in the world. The texts in this volume belong to various genres, especially legal records and letters, and span almost two thousand years. With such varied material, the work depends on the expertise of specialists in each setting, from the Sumerian of early Ur to the late Akkadian of Babylonia under the Persians. The collection brings together not only 183 transliterated texts and new translations but also introductions and commentary that place these legal documents in their historical and social contexts. A glossary of legal terms, a concordance of texts included, and an index of legal terms makes this an invaluable tool for students and scholars across disciplines. "